Perception of the ethical climate among healthcare professionals in an emergency room from southern Brazil - Carpes Lanes, Taís; de Lima Dalmolin, Graziele; Maciel da Silva, Augusto; Antunez Villagran, Camila; da Silva Caram, Carolina; Bosi de Souza Magnago, Tânia Solange (Revista Cuidarte, 2024)
Highlights• The overall ethical climate and its factors were assessed as positive, except for the physician factor, which was perceived as negative among health professionals.• The item “Physicians ask nurses for their opinion on treatment decisions” was assessed as negative, which reflects the difficulty in the relationship between nursing and medicine.• Female health professionals, over 42 years of age, with a longer training period and with a partner perceived the ethical climate as positive.• A positive perception of the ethical climate is a reflection of the ability to practice the profession and the search for improvements in patient care and organizational practices related to ethical issues.Introduction: The ethical climate is defined as the shared perception among healthcare professionals of what is ethically correct behavior and how to deal with ethical issues. Objective: To evaluate the perception of the ethical climate among health professionals working in an emergency room. Materials and Methods:   Cross-sectional study carried out with healthcare professionals working in the emergency room of a university hospital in southern Brazil. Collection took place in January 2024 through the Positive Ethical Climate Promotion Platform, through the Hospital Ethical Climate Survey-Brazilian Version instrument. The data was organized and analyzed on the Positive Ethical Climate Promotion Platform, applying descriptive statistics. Results: 71 health professionals participated in the research, in which the general ethical climate was classified as positive (M=3.73; SD=0.60). The factors were evaluated as positive, except for the medical factor (M=3.23; SD=1.16), classified as negative. Descriptively, female professionals (p=0.063), with a partner (p=0.508), aged over 42 years (p=0.047) and with training time over 17 years (p=0.072) presented high averages for positive ethical climate, however, only age showed a significant association.   Discussion: Despite the positive assessment of the general ethical climate, the importance of self-reflection and self-awareness when making ethical decisions in care is understood. Conclusion: The general ethical climate and its factors were evaluated as positive, however, the medical factor was perceived as negative.How to cite this article: Lanes, Taís Carpes; Dalmolin, Graziele de Lima; Da Silva, Augusto Maciel; Villagran, Camila Antunez; Caram, Carolina da Silva; Magnago, Tânia Solange Bosi de Souza. Percepção do clima ético entre os profissionais de saúde de um pronto-socorro do Sul do Brasil. Revista Cuidarte. 2025;16(1):e4196.  https://doi.org/10.15649/cuidarte.4196
Keywords: Ethics, Professional; Organizational Culture; Nursing; Hospital; Physicians; Emergency Medical Services